2001 IEEE/PES Transmission and Distribution Conference and Exposition. Developing New Perspectives (Cat. No.01CH37294)
DOI: 10.1109/tdc.2001.971223
|View full text |Cite
|
Sign up to set email alerts
|

Bubble evolution from transformer overload

Abstract: Bubble evolution from overloading of transformers is a concern due to possible dielectric failure. Since overloading is inevitable for short periods during peak demand periods, it is necessary to specify the limits of overloading with respect to winding hot spot temperature which determines bubble evolution. Through extensive coil model testing in the early 1990s, a mathematical equation was formulated to compute bubble evolution temperatures under a variety of conditions: moisture in insulation, gas content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 2 publications
2
63
0
Order By: Relevance
“…6, the higher the water content in paper (both cellulose and aramid paper), the lower the bubble effect initiation temperature. The results of the measurements for cellulose paper are consistent with information presented in [6,7]. Assuming the same moisture level in both types of paper, it can be concluded that the bubble effect initiation temperature is lower for aramid paper than it is for cellulose paper.…”
Section: Measurement Setupsupporting
confidence: 89%
See 1 more Smart Citation
“…6, the higher the water content in paper (both cellulose and aramid paper), the lower the bubble effect initiation temperature. The results of the measurements for cellulose paper are consistent with information presented in [6,7]. Assuming the same moisture level in both types of paper, it can be concluded that the bubble effect initiation temperature is lower for aramid paper than it is for cellulose paper.…”
Section: Measurement Setupsupporting
confidence: 89%
“…• the higher the content of gases dissolved in mineral oil, the lower the initiation temperature of bubble evolution [6,7],…”
Section: Bubble Effectmentioning
confidence: 99%
“…The scientific papers that describe the implementation of the transformer temperature monitoring systems, based either on thermal models or temperature sensor installations, and other power transformer diagnostic methods that consider the key parameters, e.g., the gases, moisture in oil, partial discharge, load current and voltage, insulation power factor and pump-fan operation, are listed in references [4], [8], [9], [10], [16], [17], [19][20], [36], [38][39], [51], [63][64][65][66], [74], [77] and [81][82].…”
Section: Transformer Loading Capacity: Basic Aspectsmentioning
confidence: 99%
“…In order for the transition from dissolved condition into a bubble to occur interfacial tension must be overcome (Oommen, 2000). In oil the increased surface tension of micro bubbles would require an increased internal pressure.…”
Section: Bubblingmentioning
confidence: 99%